Substitution and crowding-out effects of active labour market policy - Elke J. Jahn; Thomas Wagner (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Arbeitsmarkt- und Regionalpolitik, 2000)
The search model contains two matching technologies, the public employment service (PES) with its type-specific registers for workers and vacancies, and the search market where firms advertise vacancies and unemployed who have not been placed by the PES search for jobs. The placement activity of the PES increases the bargained wages, reduces active job search, decreases the number of advertised vacancies, but - compared with the laissez- faire regime - increases employment and per capita consumption. Of all the instruments of ALMP, the probabilities of a match, the portion of unskilled not interested in a job, and the hiring subsidies generate crowding-out effects. The productivity of the unskilled, (re-employment)bonuses, penalties for violations of the search rule, and the stringency of the search rule cause crowdingin effects. Assistance for problem groups is less effective than promoting active job search. – – Das Suchmodel umfasst zwei Matching-Technologien, die des PES mit typspezifischen Registern für Arbeitslose und Vakanzen und die des Suchmarkts, wo Firmen Vakanzen annoncieren und nicht Vermittelte nach Stellen suchen. Die Vermittlungstätigkeit des PES erhöht die Lohnkosten, reduziert die aktive Suche und die annoncierten Vakanzen, senkt im Vergleich zum Laissez-faire Regime die Arbeitslosenquote und steigert den Pro-Kopf-Konsum. Von den Instrumentvariablen der ALMP verdrängen die Matchwahrscheinlichkeiten, der Anteil der "Arbeitsunwilligen" und die Lohnkostenzuschüsse Arbeitsplätze. Die Produktivität der Geringqualifizierten, (Wiederbeschäftigungs-) Prämien, Sanktionen für Suchregel-Verstöße sowie die Intensität der Regeldurchsetzung senken die Arbeitslosigkeit. Die Förderung von "Problemgruppen" ist weniger wirkungsvoll als die Förderung der aktiven Jobsuche.
Keywords: J41; J63; J64; J68; 330; Matching model; active labor market policy; PES; search market; heterogeneous unemployment pool; ranking; Arbeitsmarktpolitik; Arbeitsplatzsuchmodell; Wirtschaftspolitische Wirkungsanalyse; Beschäftigungseffekt; Humankapital; Crowding out; Substitutionseffekt; Theorie